Infection with HIV and HCV enhances the release of fatty acid synthase into circulation: evidence for a novel indicator of viral infection - Aragonès Gerard; Alonso-Villaverde Carlos; Oliveras-Ferraros Cristina; Beltrán-Debón Raúl; Rull Anna; Rodríguez-Sanabria Fernando; Camps Jordi; Martín Alejandro; Menéndez Javier A; Joven Jorge (BMC Gastroenterology, 2010)
Abstract Background Fatty acid synthase (FASN) is an enzyme synthesized by the liver and plays an important role in lipogenesis. The present study aimed to investigate whether serum FASN concentration may provide a direct link between HIV and/or HCV viral infections and lipid metabolic disorders commonly observed in HIV/HCV-infected patients. Methods We evaluated serum FASN concentration in 191 consecutive HIV-infected patients in the absence or presence of HCV co-infection. For comparison, 102 uninfected controls were included. Metabolic and inflammatory phenotype was also compared with respect to the presence of HCV co-infection. Results Serum FASN concentration was significantly higher in HIV-infected patients than in healthy participants and HCV co-infected patients showed higher levels than those without co-infection. Levels were also affected by treatment regimen, but marginally influenced by virological variables. Insulin concentration was the sole variable among metabolic parameters that demonstrated a significant correlation with serum FASN concentrations. Serum alanine aminotransferase (ALT) values correlated significantly with serum FASN concentration and provided the best discrimination with respect to the presence or absence of HCV co-infection. In multivariate analysis, only ALT, monocyte chemoattractant protein-1 (MCP-1) and the presence of antiretroviral treatment regimen significantly contributed to explain serum FASN concentration in HIV/HCV co-infected patients. Conclusion Serum FASN concentration is significantly increased in HIV-infected individuals. The release of FASN into the circulation is further enhanced in patients who are co-infected with HCV. Subsequent studies should explore the usefulness of this indicator to monitor the effect of viral infections on disease progression and survival.